Accelerated Breeding Programme for Short Breeding Cycle and Early Evaluation of Neem Germplasm for Azadirachtin Content through Air-layering - Gupta, V. K.; Kumar, R. V.; Solanki, K. R.; Datta, A. (Indian Forester, 2001)
No abstract